Entrepreneurial and small business stressors, experienced stress, and well being - Perrewé, Pamela L.; Harms, Peter D.; Chang, Chu-Hsiang (Research in occupational stress and well being ;, 2020)
Volume 18 of Research in Occupational Stress and Well-Being is focused on the stress and well-being related to Entrepreneurship and Small Businesses. This volume focuses on entrepreneurial and small business owners; stress, health, and well-being as it relates to personal, work, and success outcomes. The literature linking stress with entrepreneurship and small business has been somewhat scattered to date in that stress has been treated as an antecedent of decisions to create new ventures, a frequent outcome experienced by entrepreneurs and small business owners (or self-employed businesses), and a moderator of the entrepreneurial process. We attempt to resolve some of the inconsistences theoretically and to better frame future research in this important area of study. We have seven chapters that cover topics from theory-building to context in small businesses to utilizing resources. We have divided our seven chapters into three sections. In the first section, we include three chapters that examine new theories, frameworks and future research agendas in entrepreneurship. In the second section, we have two chapters that examine contexts, specifically, heterogeneity and non-family membership in small businesses. In the final section, we have chapters that examine the important role of resources in entrepreneurship. We believe this volume offers critical analyses of research on stress and entrepreneurship as well new frameworks for future research.